Millennial’s local food consumption intention when travelling - Chua, Boon Kuan (2019)
Millennial like to travel especially Malaysian as they are visafree to many countries. They always relating their travel decision with food as a reason to explore new experiences. This trend has come out with a new word which is foodcation. This research aims to examine factors such as motivational factors, food neophobia, food involvement and attitude that effect the millennial's local food consumption intention. Along with this study, non from reprobability sampling was been applied to accumulate data spondents via the internet. The response has been successfully collected from 154 respondents. Besides that, primary and secondary data have also been adopted in this research. There is 3 analysis involve in this study such as descriptive analysis, reliabi lity test and inferential analysis from the Statistical Package for Social Science (SPSS) version 21.0. The outcomes had been tabulated and discussed in Chapter 4 and Chapter 5 had provided limitations encounter by researches and recommendations for future researches. Coming to the end of this study, it showed that food involvement and attitude has a significant relationship with the millennial local food consumption intention. Conclusion, the finding of this research hoped that it may provide some usefu l insight to parties such as the tourism board, tourism marketers, local restaurants and local authorities to have some action to improve and solve their problem.